The Everything giant book of brain-boosting puzzles: improve your mental fitness with more than 750 challenging puzzles - Timmerman, Charles (Usa Everything, 2009)
Solving puzzles is an easy way to keep mentally fit. And with more than 750 puzzles--from cryptograms and word ladders to brain teasers and sudoku--you are sure to find the perfect mental exercise in this new book! Each puzzle is designed to increase brainpower, improve concentration, and reduce memory loss.
Keywords: Puzzles